EVALUASI PROGRAM JAMINAN KESEHATAN DAERAH KABUPATEN JEPARA TAHUN 2013 - nurani, desy tegar; ., yuwanto; herawati, nunik retno (Journal of Politic and Government Studies, 2016)
Necessity to get healthy and free from unhealthy condition is a right for each human. As following up from implementation of Law No. 32 of 2004 about Healthy which is autonomized to regional government, so Jepara Regional Government participate in increasing helathy quality of society by doing one of Healthy Department’s program that is Regional Healthy Assurance (Jamkesda). It is regulated in Jepara Regent Rules No. 14 of 2012 about Implementation of Jamkesda. This research is aiming to understand the implementation of Jamkesda Program in Jepara Regency in 2013 has been conducted well or not. The type of this research is quantitative research type. Technique of data collection in this research uses Questionnaire which is distributed to the respondents and interviewing to program executor, Healthy Department Jepara Regency/City also supported by documents and archives. Technique of data analysis by using data reduction, data serving and concluding. From the result of this research, it is known that Jamkesda progam in Jepara Regency is successful enough. This can be seen from the result of the assessment towards fifth indicators measurement according to William N. Dunn that are effectiveness, suffiency, equality, accuracy and responsiveness. Theimplementation of Jamkesda program in Jepara Regency also can reach its goal as assigned in Regent Rules No. 14 of 2012 and be able to give significances to government as program executor and society as Jamkesda program participants. Significances which have been perceived by society is the existence of healthy service assurance and the decrese of society’s burdens especially in healthy service costing so that people feel to be profited. Suggestion which is recommended by researcher to government is government needs to increase program socialization which is inserted in the agenda of people acivity to accelerate information distribution and government is neccessary to validate the truth and uptate participant’s poverty status, in order to avoid misdirected of participants which can emerge social envy in society and impact to the less support from society towards implemented program run by government. Keywords: healthy, Jamkesda Program, Jepara Regency